A study of the teaching of primary prevention competencies as recommended by the Report of the Pew Health Professions Commission in bachelor of science in nursing programs and associate in nursing programs. - Payne PL (Study of the Teaching of Primary Prevention Competencies as Recommended by the Report of the Pew Health Professions Commission in Bachelor of Science in Nursing Programs & Associate in Nursing Programs, 1993)
The Report of the Pew Health Professions Commission summarized the knowledge and skills needed by health care professionals in the area of health promotion and disease prevention into three broad primary prevention competencies: (a) Care for the Community's Health, (b) Practice of Prevention and Promotion of Healthy Lifestyles, and (c) Involve Patients and Families in the Decision-making Process (O'Neil, 1993). The purposes of the study were (a) to ascertain to what extent the bachelor of science in nursing (BSN) and associate degree (AD) nursing programs are preparing practitioners for the primary prevention competencies for the year 2005 as described by the Report of the Pew Health Professions Commission, and (b) to determine if there is a difference in the nature and amount of content for primary prevention competencies taught in BSN and AD nursing programs in the Southern Regional Education Board (SREB) area. Neuman's systems model was the conceptual framework for the study. The subjects were 323 undergraduate nursing programs in the 14 states of the SREB area. A questionnaire was mailed to BSN and AD nursing programs accredited by the National League of Nursing. A 68% return rate (219 questionnaires) indicated a high degree of interest in primary prevention competencies in BSN and AD nursing programs. The nature of primary prevention was divided into 13 components. Ten of the 13 components were significantly different in BSN programs. When analysis was done for the amount of content measured in lecture hours for the three primary prevention competencies, differences were found in two of the three competencies. It was found that BSN and AD programs were significantly different in the number of lecture hours for Competency 1: Care of the Community's Health and Competency 3: Involve Patients and Families in the Decision-making Process. There was no difference in lecture hours between BSN and AD programs in Competency 2: Practice of Prevention and Promotion of Healthy Lifestyles. Recommendations included replication of the study in other regions of the country and specific methods for improving health promotion and disease prevention content and experiences in undergraduate nursing programs in the SREB region.